First Kepler results on compact pulsators - VI. Targets in the final half of the survey phase - Ostensen, R. H.; Silvotti, Roberto; Charpinet, Stephane; Oreiro, R.; Bloemen, S.; Baran, A. S.; Reed, M. D.; Kawaler, S. D.; Telting, J. H.; Green, E. M.; O'Toole, S. J.; Aerts, Conny; et al. (Monthly Notices of the Royal Astronomical Society, 2011)
We present results from the final 6 months of a survey to search for pulsations in white dwarfs (WDs) and hot subdwarf stars with the Kepler spacecraft. Spectroscopic observations are used to separate the objects into accurate classes, and we explore the physical parameters of the subdwarf B (sdB) stars and white dwarfs in the sample. From the Kepler photometry and our spectroscopic data, we find that the sample contains five new pulsators of the V1093Her type, one AMCVn type cataclysmic variable and a number of other binary systems. This completes the survey for compact pulsators with Kepler. No V361Hya type of short-period pulsating sdB stars were found in this half, leaving us with a total of one single multiperiodic V361Hya and 13 V1093Her pulsators for the full survey. Except for the sdB pulsators, no other clearly pulsating hot subdwarfs or white dwarfs were found, although a few low-amplitude candidates still remain. The most interesting targets discovered in this survey will be observed throughout the remainder of the Kepler mission, providing the most long-term photometric data sets ever made on such compact, evolved stars. Asteroseismic investigations of these data sets will be invaluable in revealing the interior structure of these stars and will boost our understanding of their evolutionary history. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Stars: oscillations; Subdwarfs; Surveys; White dwarfs